Toxicity of several botanical essential oils and their combinations against females of Aedes albopictus (Skuse) and Anopheles minimus (Theobald): Oviposition deterrent, ovicidal and adulticidal efficacies - Mayura Soonwera; Nuttavich Cotchakaew (My University, 2019)
Objective: To investigate the efficacies of 12 essential oil (EO) formulations from three Zingiberaceae plants (Alpinia galanga, Curcuma zedoaria, and Zingiber cassumunar) individually and in combination with an augmenting Eucalyptus globulus (E. globulus) EO against females of Aedes albopictus (Ae. albopictus) and Anopheles minimus (An. minimus). Methods: These formulations were evaluated for their ovicidal, oviposition deterrent and adulticidal activities against Ae. albopictus and An. minimus by a topical method, a double-choice method and a WHO susceptibility test, respectively. Results: It was found that all formulations of Zingiberaceae plants EOs augmented with E. globulus EO were more effective in oviposition deterrent, ovicidal, and adulticidal activities against the two mosquito species than all of the formulations used without E. globulus EO. Their oviposition deterrent, ovicidal and adulticidal activities were equivalent to those of 10% w/v cypermethrin. In contrast, 70% v/v ethyl alcohol as a control alone was not effective at all. The highest synergistic effect in effective repellency against Ae. albopictus was achieved by 5% Alpinia galanga EO + 5% E. globulus EO and against An. minimus was 5% Zingiber cassumunar EO + 5% E. globulus EO. Moreover, the highest synergistic effects in ovicidal activities against Ae. albopictus and An. minimus were achieved by 10% Zingiber cassumunar EO + 10% E. globulus EO and 5% Curcuma zedoaria EO + 5% E. globulus EO, respectively. For the adulticidal activities, the highest synergistic effect against two mosquitoes was achieved by 5% Curcuma zedoaria EO + 5% E. globulus EO. Conclusions: These results suggest that Zingiberaceae plant EOs augmented with E. globulus EO have a high potential to be developed into oviposition deterrent, ovicidal, and adulticidal agents for controlling populations of Ae. albopictus and An. minimus.
Keywords: Zingiberaceae; Eucalyptus globulus; Aedes albopictus; Alpinia; Insect Pest Control Strategies